Dissident Poetry in Post-Crisis Spain: A Challenge to Fluidity - Olga Bezhanova (Studies in 20th & 21st Century Literature, 2020)
The global economic crisis of 2008-9 had an especially severe impact on Spain and resulted in the publication of many works of literature that address the effects and the causes of the crisis. Daniel Macías Díaz and Antonio Rómar, two contemporary Spanish poets, belong to different artistic generations, yet their response to the devastation caused by the economic collapse centers on a rejection of the neoliberal worldview that inspired the creation of the current economic system. The poets question the rhetoric of fluidity and mobility that accompanies the implantation of the neoliberal world order and call for the creation of artistic spaces where this order can be contested.
Keywords: poetry; Spain; transnationalism; neoliberalism; Spanish literature